ENDOGENOUS SCHEDULING PREFERENCES AND CONGESTION. (29th May 2017) - Fosgerau, Mogens; Small, Kenneth
Abstract : We consider the timing of activities through a dynamic model of commuting with congestion, in which workers care solely about leisure and consumption. Implicit preferences for the timing of the commute form endogenously due to temporal agglomeration economies. Equilibrium exists uniquely and is indistinguishable from that of a generalized version of the classical Vickrey bottleneck model, based on exogenous trip‐timing preferences, but optimal policies differ: the Vickrey model will misstate the benefits of a capacity increase, it will underpredict the benefits of congestion pricing, and pricing may make people better off even without considering the use of revenues.